PERIPHRASIS: BETWEEN SYNONYMY AND PLEONAZM (Proceedings of Southern Federal University. Philology, 2012)
Oks M.V.Keywords: periphrasis, synonymy, amplification, pleonasm, perissology, political discourse.This article deals with some problems which arise from the definition of periphrasis, separating it from the similar notions of pleonasm and perissology. A special emphasis is placed on the double nature of periphrasis -synonymous and amplifying - which becomes obvious in the functions of periphrasis. The study is based on the language of modern political discourse.